3-(Hydroxyimino)imidazo[1, 2-a]pyridin-2(3H)-ylidene)-1-arylethanones as new red heterocyclic dyes: Synthesis, spectral studies, quantum-chemical investigations, and antibacterial activities. Issue 3 (March 2020) - Poormirzaei, Nazanin; Pordel, Mehdi; Yaghoobi, Elnaz; Shojaee, Saeed; Aminiyanfar, Masoud; Gonabadi, Atoosa
The synthesis, optical properties, theoretical calculations, and antibacterial activities of a series of new red heterocyclic dyes derived from imidazo[1, 2- a ]pyridine are presented. 3-(Hydroxyimino)imidazo[1, 2- a ]pyridin-2(3 H )-ylidene)-1-arylethanones are obtained from the reaction of 3-nitroimidazo[1, 2- a ]pyridine with substituted acetophenone derivatives in good yields (65%–72%). The structures are confirmed by spectral and analytical data, and the optical properties of the dyes are characterized by spectrophotometry. Density functional theory calculations are performed to provide the optimized geometries and relevant frontier orbitals. Calculated electronic absorption spectra are also obtained by the time-dependent density functional theory method. Moreover, the antibacterial activities (minimum inhibitory concentration) of the new dyes against Gram-positive and Gram-negative bacterial species are determined (minimum inhibitory concentration: 5–200 μg mL −1 ).